2005
DOI: 10.1039/b412618a
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning the degree of organic functionalization of mesoporous silica nanosphere materials via an interfacially designed co-condensation method

Abstract: A synthetic method that can fine tune the amount of chemically accessible organic functional groups on the pore surface of MCM-41 type mesoporous silica nanosphere (MSN) materials has been developed by electrostatically matching various anionic organoalkoxysilanes with the cationic cetyltrimethylammonium bromide micelles in a base-catalyzed condensation reaction of tetraethoxysilane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…The tight binding of the silica precursor to the cetyltrimethylammonium headgroup of the CTAB molecule can effectively mitigate the repulsion between these cationic headgroups and stabilize the micelle structure, therefore, resulting in a highly ordered mesostructure. 68 In contrast, weak attraction and strong repulsion interactions between TMSB or VTMS and CTAB micelles lead to large shrinkage and instability of CTAB micelles, which results in a less ordered mesostructure and smaller pore size. This demonstrates that TMSB and VTMS exhibit notable disruption effects on the final mesostructure as compared with APTES and CPTES precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The tight binding of the silica precursor to the cetyltrimethylammonium headgroup of the CTAB molecule can effectively mitigate the repulsion between these cationic headgroups and stabilize the micelle structure, therefore, resulting in a highly ordered mesostructure. 68 In contrast, weak attraction and strong repulsion interactions between TMSB or VTMS and CTAB micelles lead to large shrinkage and instability of CTAB micelles, which results in a less ordered mesostructure and smaller pore size. This demonstrates that TMSB and VTMS exhibit notable disruption effects on the final mesostructure as compared with APTES and CPTES precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al also reported a similar organosilane-induced morphology transition. 199,200 Furthermore, the preparation of mesoporous nanoparticles with phenylene-bridged silsesquioxane frameworks was reported by Cho et al 201 By utilizing a binary surfactant system of a poly(ethylene oxide)-b-poly(D,L-lactic acid-co-glycolic acid)-b-poly(ethylene oxide) (PEO-b-PLGAb-PEO) triblock copolymer combined with fluorinated surfactants, the particle size ranges between 50 nm and 1¯m. The obtained nanoparticles, however, aggregate in aqueous solution, presumably because of the hydrophobic character of the phenylene-bridged silsesquioxane frameworks.…”
Section: Novelties In Surfactant-templated Mesoporous Materialsmentioning
confidence: 99%
“…Pores size of 10 and 300 Å have been reported along with different porous structured nanophases, using a replica of the surfactant template ( Figure 11). During the synthesis of mesoporous SiO2 NPs, fine synthetic control will result in high surface areas with well controlled particle sizes and shapes that render these NPs very interesting [25][26][27][28][29]. …”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…The synthesis of mesoporous silica NPs is done by modifying the Stöber method, adding surfactants that behave like templates, and will later be chemically or thermally removed [25][26][27] (Figure 10). Pores size of 10 and 300 Å have been reported along with different porous structured nanophases, using a replica of the surfactant template ( Figure 11).…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%